Creating a Connected Future Through Information and Digital Literacy: Strategic Directions at The University of Queensland Library*. Issue 1 (2nd January 2018) - Hallam, Gillian; Thomas, Amberyn; Beach, Bill
Abstract: As knowledge-intensive institutions, universities face many challenges resulting from today's highly dynamic technological environment. While the ways in which learners and researchers engage with digital information resources are complex and diverse, there is a keen awareness of the varying levels of information and digital literacy skills amongst students and academic staff. A university-wide approach to skills development, involving all stakeholders, has been recommended as a valid approach to addressing some of the issues. At the University of Queensland, the Library has led the way with the development of a future-focused strategic framework for information and digital literacy to help shape the University's academic policies and practices. After reviewing the principles that underpin the strategic framework (collaboration, alignment, innovation, sustainability and evaluation), the paper presents some of the key strategies which have been introduced to encourage the development of digital skills in the contexts of undergraduate teaching and learning, digital scholarship and eResearch. It is argued that there is great potential for library staff to extend their reach and serve as digital facilitators, connectors and collaborators, making a significant contribution to successful outcomes in many areas of contemporary academic life.